When ecological functions are more important than richness: A conservation approach - Vagner Santiago do Vale; Ivan Schiavini; Ana Paula de Oliveira; André Eduardo Gusson (African Journal of Environmental Economics and Management, 2022)
In this work, we utilize the assessment of functional groups (FG) and functional diversity (FD) to evaluate and compare the ecological functions of two types of dry forest of South Eastern Brazil. Hence, we hypothesized that forests with different species richness could have similar FD and FG, but distinct ecological functions. The floristic composition from two physiognomies (deciduous and semideciduous forests) of six tree communities was carried out in the state of Minas Gerais, South Eastern Brazil. The inventory was pooled together considering the traits of species such as: shade tolerance, deciduousness and desiccation tolerance of seeds; one structural feature: position on vertical strata; and two animal-plant interactions: dispersal syndrome and pollination syndrome. We chose two multivariate analyses to infer to the functional groups and used the one-way ANOVA to test differences between the abundance of the groups in the two physiognomies. The difference in FD between the two physiognomies was tested using the Shannon diversity index and the Hutcheson t test. Both physiognomies had the same FG and FD. The most abundant group in the semi-deciduous forest was G1, which occupied lower communities (shade tolerant and perennial), whereas G4 for deciduous forest was anemochoric and autochoric of superior community strata that is light demanding. The functional diversity between the two physiognomies showed that semi-deciduous contains more species than the deciduous ones (75% more species) and are more diverse with the Shannon index of 3.3. Hence, the number of species alone had little importance when we analysed functions in ecosystems. The more abundant groups in each forest had completely different traits and were complementary in their functions to the ecosystem. In this case, a species-rich and less- species rich system provided different key functions to the ecosystem despite their differences in species richness, diversity or physiognomic type. The use of species-rich and less- species- rich areas would present different key groups, and as such, this may be the best alternative to choose priority areas for conservation.